2009
DOI: 10.1097/01.ede.0000362647.70007.cb
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling of Personalized Exposure Dynamics: The Case of Pesticide Use in Small-Scale Agricultural Production Landscapes of the Developing World

Abstract: Background: Pesticide poisoning is a global health issue with the largest impacts in the developing countries where residential and small-scale agricultural areas are often integrated and pesticides sprayed manually. To reduce health risks from pesticide exposure approaches for personalized exposure assessment (PEA) are needed. We present a conceptual framework to develop a spatial individual-based model (IBM) prototype for assessing potential exposure of farm-workers conducting small-scale agricultural produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Agricultural safety and the resulting environmental and health problems from pesticide application are increasingly attracting global attention [18,21,42]. However, a large input of pesticides leads to excessive residues that adversely affect the quality of agricultural goods [52].…”
Section: Negative Effects Of Agrochemicals Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural safety and the resulting environmental and health problems from pesticide application are increasingly attracting global attention [18,21,42]. However, a large input of pesticides leads to excessive residues that adversely affect the quality of agricultural goods [52].…”
Section: Negative Effects Of Agrochemicals Residuesmentioning
confidence: 99%
“…Pesticide residues affect human health. In fact, pesticide application has become a great threat to human health [12,25,42,54]. Studies have shown that long-term lowdose exposure to pesticides leads to the development of respiratory diseases such as asthma [30].…”
Section: Negative Effects Of Agrochemicals Residuesmentioning
confidence: 99%
“…These approaches were often seen in mobility-related exposure studies using empirical or experimental traffic data for specific individuals [43,50]. Leyk, et al (2009), presenting a spatial individual-based model prototype for assessing potential pesticide exposure of farm-workers with their individual level track of movement and activities. Similarly, more complex modeling tools were developed for quantification of human exposure to traffic-related air pollution within distinct micro-environments by using GPS trajectory analysis of the individuals in the city area [10,24].…”
Section: Modeling Of Individual's Exposure Degreementioning
confidence: 99%
“…Figure 1 illustrates the ABM used in this paper. [45] In this framework, spatial data of the changing concentration patterns of the environmental stress factors are the key pre-set inputs that build up the natural aspects of the system (center layer in Figure 1). A specific map will be used to represent the city with buildings, streets, shops, green areas, etc.…”
Section: Model Structurementioning
confidence: 99%
“…These movements may correspond to different needs including foraging for food, searching for sexual partner, colonization of new habitats or juvenile dispersal. The spatial activity pattern of an individual is often considered as one of the drivers of its exposure to chemicals because it determines partly both the frequency and intensity of contact with the pollutant and thus the quantity that can be transferred into a receptor (Leyk et al 2009;Loos 2011;Spurgeon et al 2011). According to Loos (2011), the spatial variation in habitat quality (including food availability), the habitat patch connectivity, population density and foraging behavior govern the home range of an animal, the time it spends per unit area within its home range and also its diet in terrestrial ecosystems.…”
Section: B Spatial Patterns Of Small Mammal Exposure To Armentioning
confidence: 99%